Intensive English learning methods and their impact on language proficiency - Dildora Safarova; Nulifar Xolmurodova; Nozima Kuchkarova (Science and Education, 2025)
In this study, the effectiveness of the Accelerated Communicative Learning Method in English language acquisition is examined. The research analyzes the impact of intensive learning techniques on students’ fluency, confidence, and retention of vocabulary and grammar. Various aspects of modern language education are considered, including interactive teaching strategies and technological tools. The study provides a compaarative analysis of traditional and intensive learning methods, highlighting their advantages and limitations. Furthermore, the article presents the results of an experimental study that evaluates the role of educational equipment in enhancing linguistic competence. The effectiveness of different tools, such as interactive whiteboards, headsets, and gamified learning platforms, is assessed. The findings demonstrate that an immersive and communicative approach significantly improves students’ language proficiency. The research provides practical recommendations for implementing intensive methodologies in language education to achieve better learning outcomes.